Under a summer sky [large type] : a Savannah romance - Carlson, Melody (Carlson, Melody. Follow your heart, 2017)
High school art teacher Nicole Anderson is looking forward to a relaxing summer in Savannah, house-sitting and managing an art gallery for a family friend. The house is luxurious in a way that only old money could make it, and the gallery promises interesting days in a gorgeous setting. Yet it isn't long before her ideal summer turns into more than she bargained for: a snooty gallery employee who's determined to force her out, a displaced adolescent roosting in the attic, and two of Nicole's close childhood friends -- who also happen to be brothers -- vying for her attention.